China panic Australia's alternative to paranoia and pandering - Brophy, David J. (La Trobe University Press in conjuntion with Black Inc., 2021)
When he visited Australia in 2014, Chinese president Xi Jinping said there was an 'ocean of goodwill' between our country and his. Since then that ocean has shown dramatic signs of freezing over. Australia is in the grip of a China Panic. How did we get here and what's the way out? We hear, weekly, alarming stories of Chinese influence, interference or even espionage - in politics, on campus, in the media, in community organisations and elsewhere. The United States now sees China as a strategic rival, and pressure on Australia to 'get tough on China' will only intensify. While the xenophobic right hovers in the wings, some of the loudest voices decrying Chinese subversion come, unexpectedly, from the left. Aligning themselves with hawkish think tanks, they call for new security laws, increased scrutiny of Chinese Australians and, if necessary, military force - a prescription for a sharp rightward turn in Australian politics. In this insightful critique, David Brophy offers a progressive alternative. Instead of punitive measures that restrict rights and stoke suspicion of minorities - moves that would only make Australia more like China - we need democratic solutions that strengthen Australian institutions and embrace, not alienate, Chinese Australians. Above all, we need forms of international solidarity that don't reduce human rights to a mere bargaining chip
Keywords: Außenpolitik; China; Australien; Australia / Foreign relations / China; China / Foreign relations / Australia; Diplomatic relations; Australia